Que espiritismo é esse? Fernando do Ó e contexto religioso de Santa Maria - RS (1930-1940) - Mattos, Renan Santos (2013)
Before the pluralization process of the Brazilian religious field in the end of nineteenth century showed the constitution of a competitive market for goods of salvation among the different religious current, this dissertation investigates the trajectory of Fernando Souza do Ó. He was an important Spiritist leader in the city of Santa Maria in the process of organization of the local Spiritist movement, when he assumed the role of "propagator" of the doctrine at the city in context from 1930 to 1940. Accordingly, we start with the concern of how their ideas represented an insertion strategy for the Spiritualist movement in the city of Santa Maria, and for that, we turn to the set of written by the author connected in lay press (Diary of Interio) in order to understand how Fernando do Ó established the dialogue with different people that made this scenario, allowing , from his performance , highlight the conflicts and competitions existing in the religious field in the City of Santa Maria . The dissertation is linked to the search Migration and Work of the PPGH/UFSM when analyzes the constitutive relations of a field of disputes between new labor organizations and the insert that character into realities of migration process. It consists of a biography and career chapter, where we search to answer who was Fernando do Ó, and what legitimizes as an important character of Spiritism in the city. The second part approach the Spiritualist Experience, aims to present the creation of spiritualism, featuring the theoretical questions posed by Alan Kardec and specificities of the construction of Spiritualist movement in the city. Finally, we approach the political and philosophical positions as assumed by Fernando do Ó in the newspaper, referencing the interpretations of of its historical time. Keywords: Spiritism. Fernando do Ó. Biography. Santa Maria - RS